Image-potential states on stepped Cu (001) surfaces - Roth, Manfred; Pickel, Martin; Wang, Jinxiong; Weinelt, Martin; Fauster, Thomas (Applied Physics B-Lasers and Optics, 2002)
Image-potential states on Cu (117) and Cu (119) surfaces were studied by means of two-photon photoelectron spectroscopy. The regular array of steps generates a lateral potential on the vicinal surfaces, which modifies the surface-electronic structure. Compared to Cu(001), the band bottom of the n = 1 image-potential states shifts by 40 meV to lower binding energy. The periodicity of the step-induced superlattice manifests itself as back-folding of the n = 1 and 2 dispersion bands. At the surface Brillouin zone boundary a mini-gap opens with a width of 135 meV for the first image-potential state on Cu (117). On the vicinal surfaces the lifetime of the image-potential states is reduced by a factor of three as compared to Cu (001). This is attributed to a narrowing of the surface-projected bulk-band gap when projected along the [I In] direction. While the dephasing rate of the first image-potential state is close to the decay rate, higher members of the Rydberg-like series show negligible dephasing.